The potential of miscanthus to sequester carbon in soil : a study of carbon dynamics in soil aggregates - Dondini, Marta (Trinity College (Dublin, Ireland). Department of Botany, 2010)
The growing of bioenergy crops has been widely suggested as a key strategy in mitigating anthropogenic CO2 emissions. However, the full mitigation potential of these crops cannot be assessed without taking into account their effect on soil carbon (C) dynamics. Here I analyzed the potential of Miscanthus, a bioenergy crop, to sequester C in the soil. I studied the effect of land use change from Miscanthus to arable and grassland on the total SOC content, as well as on the C associated with the soil fractions. Finally, in order to predict the potential of Miscanthus to sequester C in the soil, I compared direct measurements of soil organic carbon fractions to soil C model predictions made by RothC and a cohort model.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin